Ocular immune privilege - Zhou, Ru (Biology Reports, 2010)
The eye attempts to limit local immune and inflammatory responses to preserve vision. This phenomenon, known as ocular immune privilege, is mediated by a combination of local and systemic mechanisms. While immune privilege is believed to protect the eye from day-to-day inflammatory insults, it is not absolute and its mechanisms are still incompletely understood.